The Behavior of Drug Providers in the Petik Laut Tradition of Coastal Communities - Ririanty, Mury; Rif’ah, Erwin Nur; Dwiastuti, Winda Ariyanti (Disease Prevention and Public Health Journal, 2024)
Background: Petik Laut is a tradition that is manifested in the form of rituals with aim of being a way of express gratitude to God Almighty. Petik Laut tradition has changed from what was originally simple with only holding ceremonies, ritual prayers. Petik Laut tradition has become lively with the addition of the Petik Laut carnival, this is where the loophole for drug abuse behavior occurs in the Petik Laut tradition. Method: This researched was a qualitative study with a case study approach. Determination of the main informants used the snowball sampling technique. The main informants in the study were three people who consumed drug abuse as drug providers. Results: 1) All key informants had diverse thoughts about the Petik Laut tradition which was interpreted as a from of safety, thanksgiving, celebration and public entertainment. 2) Informants said that important people as references were friends who were both doers in drug abuse behavior in Petik Laut tradition. 3) Informants stated that facilities for obtained drugs were by buying them themselves at specialty store sell alcoholic beverages, at drug stores, and by an undisclosed seller. 4) Social-cultural values of all informants considered drink alcohol as a culture same drink herbal medicine, consumed in a addition to carried out the Petik Laut tradition. Religious value because there is opposition to understanding of the majority of religious belief there, namely Islam. Conclusion: Drug abuse behavior in the Petik Laut tradition is not related to the social and cultural traditions of the Petik Laut.